2018
DOI: 10.1371/journal.pone.0197967
|View full text |Cite
|
Sign up to set email alerts
|

Renal resistive index as an early predictor and discriminator of acute kidney injury in critically ill patients; A prospective observational cohort study

Abstract: BackgroundAcute kidney injury (AKI) complicates shock. Diagnosis is based on rising creatinine, a late phenomenon. Intrarenal vasoconstriction occurs earlier. Measuring flow resistance in the renal circulation, Renal Resistive Index (RRI), could become part of vital organ function assessment using Doppler ultrasound. Our aim was to determine whether RRI on ICU admission is an early predictor and discriminator of AKI developed within the first week.MethodsIn this prospective cohort of mixed ICU patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 62 publications
3
31
1
1
Order By: Relevance
“…Previous studies found that high RRI was a predictor of AKI. Because vasopressor support showed the strongest independent relation with a high RRI and because high RRI predicts the development of AKI during the first week of ICU admission (9), our findings could indicate that too much vasopressors might unnecessarily increase renal vasoconstriction and subsequently contribute to the development of AKI. Measuring RRI using bedside ultrasound could be part of the assessment of vital organ status and function.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies found that high RRI was a predictor of AKI. Because vasopressor support showed the strongest independent relation with a high RRI and because high RRI predicts the development of AKI during the first week of ICU admission (9), our findings could indicate that too much vasopressors might unnecessarily increase renal vasoconstriction and subsequently contribute to the development of AKI. Measuring RRI using bedside ultrasound could be part of the assessment of vital organ status and function.…”
Section: Discussionmentioning
confidence: 83%
“…The study was performed at Amsterdam UMC, Vrije Universiteit Amsterdam, Department of Intensive Care Medicine, Amsterdam, the Netherlands, and is part of a larger project that additionally determines the predictive value of RRI for the development of AKI (9). The study was approved by the Ethical Board of the VUmc, which allowed a deferred consent procedure to obtain signed consent for the use of the data (VU University Medical Centre Protocol Record METC-2015.025).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of blood flow velocity, not dependent on circumference or wall thickness, revealed a significant increase in EDV at 3 and 5 weeks in the WT mice subjected to carotid ligation. PI and RI are non-dimensional velocity measurements used to assess organ perfusion in clinical research and to assess vascular impedance and large artery stiffness in experimental cardiovascular research [37,45]. Interestingly, a gradual decrease in PI and RI over time was observed in the Pcsk6 −/− mice, which could not be detected in the WTs.…”
Section: Discussionmentioning
confidence: 99%
“…Normal values of the RRI are reported to be between 0.60 and 0.70 4 . The diagnostic and prognostic value of the RRI has been studied in several clinical conditions such as renal transplantation, 5 renal allograft survival, 6 atherosclerotic renovascular disease, 7 acute kidney injury, 8 chronic kidney disease, 9 hypertension, 7 diabetes mellitus, 10 arterial stiffness, 11 coronary artery disease, 12,13 and heart failure 14 . Impaired renal hemodynamics, assessed by increased RRI, were found to be associated with increased cardiovascular risk 15 .…”
Section: Introductionmentioning
confidence: 99%